Estimating ancient seawater isotope compositions and global ocean redox conditions by coupling the molybdenum and uranium isotope systems of euxinic organic-rich mudrocks. (1st December 2020) - Lu, Xinze; Dahl, Tais W.; Zheng, Wang; Wang, Su; Kendall, Brian
Abstract: The sedimentary Mo and U isotope systems have been commonly used as novel global ocean redox tracers due to their long oceanic residence times and redox-sensitive behavior. However, local sedimentary environments and global ocean redox conditions both influence the Mo and U isotope compositions of euxinic organic-rich mudrocks (ORM). Here, we further develop the coupled use of Mo and U isotope data from euxinic ORM to more robustly infer coeval global ocean redox conditions. We measured δ 238 U from eight late Neoproterozoic to middle Paleozoic ORM units that have previously reported Mo isotope and Fe speciation data. Integration of our new data with previously published Proterozoic and Phanerozoic Mo and U isotope data reveals that there is no overall correlation between the Mo and U isotope compositions of euxinic ORM. This observation confirms that the extent to which local versus global environments influenced the preserved Mo and U isotope compositions in ORM was variable. Individual ORM units can have negative, positive, or no correlation between δ 98 Mo and δ 238 U. A negative correlation between δ 98 Mo and δ 238 U in the Upper Devonian Kettle Point Formation is similar to the observations from modern euxinic basins, reflecting a major control on the Mo-U isotope systematics by changes in the local depositional environment, such as bottom-water sulfide concentrations. A positive correlation between δ 98 Mo and δ 238 U observed in the Upper Ordovician Fjäcka Shale is best explained by changes in global ocean redox conditions that simultaneously shifted the Mo and U isotope compositions of the global seawater and the Fjäcka Shale ORMs in the same direction. No correlations between δ 98 Mo and δ 238 U for euxinic ORM may be caused by specific local depositional changes, a lack of or a combination of local and global environmental changes, and/or is an artifact of limited data. For example, a vertical trend (variable δ 98 Mo but similar δ 238 U) is shown by most samples from Member IV of the Ediacaran Doushantuo Formation, implying a strong influence on the Mo isotope data by an Fe-Mn particulate shuttle. A horizontal trend (similar δ 98 Mo but variable δ 238 U) is observed from the Paleoproterozoic Zaonega Formation, implying that relatively constant bottom water sulfide concentrations caused similar magnitudes of Mo isotope fractionations whereas other factors (e.g., U reduction pathways, aqueous U species, productivity) were responsible for variable U isotope fractionations. Relatively constant elemental concentrations and isotope compositions from the Tanezzuft Formation are indicative of stable conditions at local and global scales. We further propose a method to estimate the coeval seawater Mo and U isotope compositions based on a coupled Mo-U isotope mass balance model and the observations from modern euxinic basins. The coupled Mo-U isotope data from euxinic ORMs provide more insights on the local and global environmental controls on the preservation of both isotope systems than previously realized. Our study highlights the importance of examining the local depositional environment and using large datasets of coupled Mo-U isotope compositions from euxinic ORM intervals to reconstruct paleocean redox conditions.